2014
DOI: 10.2147/opth.s67589
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endogenous endophthalmitis in Vietnam: a randomized controlled trial comparing vitrectomy with silicone oil versus vitrectomy alone

Abstract: Background/aimsTo compare treatment outcomes with and without silicone oil tamponade in patients undergoing pars plana vitrectomy (PPV) for severe endogenous bacterial endophthalmitis (BEE).MethodsOne hundred and eight consecutive patients with severe BEE (defined by the absence of pupil red reflex at presentation and/or dense vitreous opacity on ultrasound and no improvement after 24–36 hours of medical treatment) were randomly assigned to two treatment groups: Group 1, standard PPV with intravitreal antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 21 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…(2003) or Do et al. (2014) showed no significant differences for the analysis of RRD. However, the I 2 analysis in the majority of the comparisons showed moderate heterogeneity in the pooled studies, indicating the effect of different tamponades in control groups.…”
Section: Resultsmentioning
confidence: 92%
“…(2003) or Do et al. (2014) showed no significant differences for the analysis of RRD. However, the I 2 analysis in the majority of the comparisons showed moderate heterogeneity in the pooled studies, indicating the effect of different tamponades in control groups.…”
Section: Resultsmentioning
confidence: 92%
“…Ratra et al found a significantly improved chance for anatomical and functional success with vitrectomy [ 7 ]. In a randomized trial performed on bacterial EE cases, silicone oil endotamponade has significantly increased the rate of success at 9 months [ 82 ]. In a case series of EFE, VA increased by 2 lines in 25% of eyes after intravitreal injections and in 71% of eyes after vitrectomy plus intravitreal injections [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the overall success rate defined as visual acuity ≥ counting fingers at 1 meter, attached retina, without silicone oil at 9 months follow up was higher in the silicone oil group than the vitrectomy alone group. 57 …”
Section: Endogenous Bacterial Endophthalmitismentioning
confidence: 99%